Encyclopedia of developing regional communities with information and communication technology - Marshall, Stewart; Taylor, Wallace; Yu, Xing Huo (Idea Group Reference, 2006)
"This encyclopedia provides a thorough examination of concepts, technologies, policies, training, and applications of ICT in support of economic and regional developments around the globe"--Provided by publisher.